2021
DOI: 10.3389/fimmu.2021.717723
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Analysis of the Colonic Flora Diversity, Short Chain Fatty Acid Metabolism, Transcripts, and Biochemical Indexes in Heat-Stressed Pigs

Abstract: Heat stressed pigs show typical characteristics of inflammatory bowel disease (IBD). However, little is known about the pathogenesis of heat stress (HS)-induced IBD in pigs. In this study, we determined the effects of HS on colon morphology, intestinal microbiota diversity, transcriptome genes (transcripts), and short chain fatty acids (SCFAs) metabolism in pigs. In addition, the correlation among these parameters was analyzed by weighted gene co-expression network analysis. Results showed that the liver and k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 67 publications
(81 reference statements)
0
27
0
Order By: Relevance
“…In our study, none of the four tested culture media contained mucin as an ingredient which could potentially lead to nutrient starvation as it is an important growth factor for numerous microorganisms, especially within the Firmicutes phyla 76 . Moreover, GM, FM, and CFBM promoted the growth of Clostridium sensu stricto 1 , an opportunistic pathogen, which plays a role in the occurrence of intestinal inflammation and can be associated with decreased microbial SCFAs production 77 . Thus, the decrease in SCFAs production observed in our study may have been associated with increased Clostridium sensu stricto 1 abundance.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, none of the four tested culture media contained mucin as an ingredient which could potentially lead to nutrient starvation as it is an important growth factor for numerous microorganisms, especially within the Firmicutes phyla 76 . Moreover, GM, FM, and CFBM promoted the growth of Clostridium sensu stricto 1 , an opportunistic pathogen, which plays a role in the occurrence of intestinal inflammation and can be associated with decreased microbial SCFAs production 77 . Thus, the decrease in SCFAs production observed in our study may have been associated with increased Clostridium sensu stricto 1 abundance.…”
Section: Discussionmentioning
confidence: 99%
“…Proteobacteria are the most consistently reported microbiota related to obesity in the aforementioned systematic research (Xu et al, 2022). Clostridium sensu stricto is a putative opportunistic pathogen that can lead to decreased SCFA levels and intestinal inflammation (Hu et al, 2021). In swine, correlation heat map analysis demonstrated that Clostridium sensu stricto is strongly connected with total cholesterol and the pathogenesis of heat-stress-associated inflammatory bowel disease (Hu et al, 2021).…”
Section: Enterotype 2 Metabolism and The Phenome Of Depressionmentioning
confidence: 99%
“…After the intestinal injury, D-lactic acid in the intestine will enter the peripheral blood through the intestinal mucosa ( 21 ). As shown in Figure 6 , compared with the control group, TGEV infection significantly increased the D-lactic acid content in the serum of weaned piglets ( P < 0.05).…”
Section: Resultsmentioning
confidence: 99%